'Give me the meat, the child said': Cultural practice among the children of the Baka hunter-gatherers. Issue 1 (May 2016) - Sonoda, Koji
Abstract : Using video-recorded data, this study investigates the use of the third-party position by cameroonian Baka hunter-gatherer children in talk-in-interaction with adults, in relation to butchering bush meat. Baka children often support the meat-cutting activity, which allows them to hear adult talk and to discuss social events with adults. The findings demonstrate that children utilised their third-party position to avoid trouble in talk with adults, and used overheard adults' utterances to create, apply, and reconfirm the identity categories of 'adult' and 'child'. overall, these findings indicate that Baka children use quiet observation of adults to construct participation frameworks that incorporate both adults and themselves.